Comparative study of continuous-stirred and batch microwave pyrolysis of linear low-density polyethylene in the presence/absence of HZSM-5. (1st August 2021) - Fan, Liangliang; Liu, Lei; Xiao, Zhiguo; Su, Zheyang; Huang, Pei; Peng, Hongyu; Lv, Sen; Jiang, Haiwei; Ruan, Roger; Chen, Paul; Zhou, Wenguang
Abstract: A continuous-stirred microwave pyrolysis (CSMP) reactor was designed for linear low-density polyethylene (LLDPE) conversion. Its performance was compared with the batch microwave pyrolysis (BMP) under identical conditions. During the pyrolysis, the continuous-stirred system generated more condensate products with higher selectivity in long carbon chains (C14 –C20 ), whereas the batch system was more selective for gas products with a higher proportion of methane. An ex-situ catalytic bed with HZSM-5 was assembled to upgrade pyrolysis vapors, corresponding to improved gasoline-range hydrocarbons and propylene production. The comparison of catalytic processes showed similar product yields for both configurations, with differences primarily on chemical species selectivity. For instance, the products from the continuous-stirred system had narrower carbon number distribution (C7 –C10 ) and higher selectivity to mono-aromatics (72.3%). The proposed pathways for LLDPE conversion from the two systems showed slight differences in the thermal cracking process but similarities in the catalytic cracking process. During the catalytic processes, the potential net energy gain was 34.16 MJ/kg for CSMP and −38.86 MJ/kg for BMP, compared with the non-catalytic processes, when the figures were 9.85 MJ/kg and −42.86 MJ/kg, respectively. Graphical abstract: Image 1 Highlights: A comparison between continuous-stirred and batch microwave pyrolysis was studied. Hydrocarbons from the continuous pyrolysis showed narrower carbon atom distribution. Up to 98.0% gasoline-range hydrocarbons were obtained from the continuous system. LLDPE conversion mechanisms for the two systems were elaborated. The net energy gain from the catalytic continuous pyrolysis was 34.16 MJ/kg.